Integrative Moral Education Concept and Method: Ibnu Abi Al-Dunya’s Thoughts - Lanye, Umar bin Makka; Azwar, Azwar; Aswar, Aswar; Amirullah, M. (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2023)
This research was conducted with the aim to examine the specifics and in-depth of the concept of integrative moral education in the perspective of Ibnu Abi al-Dunya and recommend the formulation of implementative methods that can be applied in the moral education based on his perspective. This research used qualitative methods by using a content analysis approach to the book of Makārim al-Akhlāq by Ibnu Abi al-Dunya. The results revealed that the moral education in the concept of Ibnu Abi al-Dunya is an ongoing process of education in instilling noble nature, which is based on true faith and tauḥīd, in order to form a godly person, has the perfection of faith. True moral education is moral education that is inseparable from the education of faith and faith. This is because noble morals must be based on faith, while the perfection of faith is reflected in noble morals. Moral education methods should be emphasized on more substantial aspects of emphasis rather than just being formalistic and verbal. The methods (uslub) of moral education in the concept and thinking of Ibnu Abi al-Dunya are pioneered as follow: (1) al-qudwah wa al-uswah, good examples; (2) al-targīb wa al-tasywīq, makes a person love and like something; (3) at-tarhīb, threat or punishment; (4) al-ta'awwud, of habituation; (5) al-wa'zhu wa al-naṣīḥah, advice and direction; (6) al-ḥiwār, discussion.